ANALISIS LITERATUR DUKUNGAN KELUARGA TERHADAP KUALITAS HIDUP LANSIA DI INDONESIA - Winata, Septiany Putri; Nugraheni, Indah Listya; Suparmi, Suparmi (Jendela Inovasi Daerah, 2025)
Elderly people are individuals who are over 60 years old and generally experience a decline in physical and psychological abilities. In this case, the family has an important role in providing support to improve the quality of life of the elderly in a stable and sustainable manner. The aim of this research is to determine the effect of family support on the quality of life of the elderly. This research uses a literature review approach by searching for relevant scientific articles within the last ten years. Data is collected through the Publish or Perish application using keywords appropriate to the topic. From this search, 150 articles were obtained. Next, an identification and screening process is carried out using predetermined inclusion and exclusion criteria. After the selection process, 10 articles were obtained which were deemed to be most appropriate to the research focus, namely regarding the influence of family support on the quality of life of the elderly. Data analysis was carried out narratively, by grouping findings based on the form of family support provided to the elderly. Based on the results of this analysis, it is known that family support has a significant influence on improving the quality of life of the elderly. Forms of support such as attention, affection and positive social interactions can reduce feelings of loneliness in the elderly and provide emotional encouragement that is important for their well-being.